An Unusual Case of Subclinical Peripheral Neuropathy and Cervical Spondylosis in Atopic Myelitis - Alev Leventoglu; Pelin Ozlu; Ferda Ince (Case Reports in Neurological Medicine)
Many cases of atopic myelitis have been reported in Japan; however very few were described in western countries. An 82-year-old woman with a past medical history of atopic dermatitis and asthma presented with progressive paresthesia (tingling) of both hands and tetraparesis. Before the onset of neurological symptoms, she complained of ichthyosis of both legs for 5 weeks. Magnetic resonance imaging demonstrated multisegmental degenerative arthritis, degenerative disc disease, and abnormal spinal cord signal intensity over several cervical segments, suggesting the diagnosis of myelitis. Total serum IgE level was elevated. Nerve conduction studies revealed asymmetric axonal sensorimotor neuropathy. The cerebrospinal fluid specimen showed lymphocytic pleocytosis and elevated protein level. Based on clinical, imaging, and laboratory findings, atopic myelitis was diagnosed. The diagnosis of atopic myelitis should be considered in myelopathy patients with history of atopy and elevated serum IgE levels.